Güzel Sanatlar Eğitim Fakültesi Öğrencilerinin Dijital Sanat ve Resme İlişkin Görüşlerinin İncelenmesi – Bir Fenomenolojik Desen Çalışması. - Boydaş, Okan; Duran, Fikriye (Cumhuriyet Üniversitesi Fen-Edebiyat Fakültesi Sosyal Bilimler Dergisi, 2026)
The aim of this research is to determine the views of the students of the Faculty of Fine Arts Education on Digital Art and Painting. In the research, qualitative research method and phenomenology approach, which is one of the patterns of this method, was used. The study group consists of prospective students who studied at a Faculty of Education. Semi-structured interviews were used as a data collection tool and a pre-prepared interview form was used in the interviews. The interviews were audio-recorded with the permission of the participants, and then these recordings were transcribed and analysed. Purposive sampling was used for the study group of the research. In order to provide practicality to the research, typical case sampling, one of the purposeful sampling methods, was preferred. After the process of creating themes, categories and codes, content analysis was applied and care was taken to ensure validity and reliability. According to the findings of the research, prospective students are determined what the basic qualities of digital art are related to the art of painting Within the scope of the study, it is emphasised how digital science can be understood at the conceptual and theoretical level. In addition, how the conceptual and theoretical dimensions of digital science can be interpreted has been analysed. This discipline, which brings together different universal forms and technical expressions, offers a field that questions the individual's relations with his environment, information, technology and aesthetic understanding. Different dimensions of digital art are analysed with a multidimensional approach by taking a broad perspective. The fact that digital art saves time in the design process, accelerates the production stages and allows different forms of expression is evaluated among the positive aspects of this field in terms of painting education.